2018
DOI: 10.18092/ulikidince.353903
|View full text |Cite
|
Sign up to set email alerts
|

G20 Ülkeleri̇ni̇n Yeni̇lenebi̇li̇r Enerji̇ Etki̇nli̇ği̇ni̇n Dengeli̇ Performans Ağirliklari Ve Veri̇ Zarflama Anali̇zi̇ İle Değerlendi̇ri̇lmesi̇

Abstract: Yenilenebilir enerji son yıllarda sürdürülebilir kalkınma ve çevre ile ilgili çalışmalarda çok fazla kullanılan bir terim olmuştur. Bu çalışmanın amacı G20 ülkelerinin yenilenebilir enerji performansını veri zarflama analizi (VZA) ve dengeli performans ağırlıkları yöntemiyle ortaya koymaktır. VZA performans ölçümü için kullanılan parametrik olmayan ve güçlü bir tekniktir. VZA'da girdi ve çıktı ağırlıklarının belirlenmesi çalışmanın sonucunu büyük ölçüde değiştirebilecek önemli bir aşamadır. Ağırlıkların belirl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0
1

Year Published

2020
2020
2021
2021

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 8 publications
0
4
0
1
Order By: Relevance
“…Whereas, Republic of Korea, China, South Africa, Indonesia, and India are at the bottom. Supporting this finding, Australia, the United States, Germany, and Canada are among the top five countries in the study of Küpeli and Alp (2018), which evaluates the renewable energy performance of G-20 countries with balanced performance weights method. On the other hand, South Africa, China, Indonesia, and India are among the five countries with the lowest performance.…”
Section: Discussionmentioning
confidence: 71%
See 2 more Smart Citations
“…Whereas, Republic of Korea, China, South Africa, Indonesia, and India are at the bottom. Supporting this finding, Australia, the United States, Germany, and Canada are among the top five countries in the study of Küpeli and Alp (2018), which evaluates the renewable energy performance of G-20 countries with balanced performance weights method. On the other hand, South Africa, China, Indonesia, and India are among the five countries with the lowest performance.…”
Section: Discussionmentioning
confidence: 71%
“…Moreover, Tan et al (2017) and Nilashi et al (2018) adopt the Adaptive Neuro-Fuzzy Inference System (ANFIS) approach to measure sustainability performance at the country level. Küpeli and Alp (2018)…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Ancak fosil yakıt rezervlerinin azalması, çevre kirliliğine neden olması, toplumda oluşan çevre bilinci ülkeleri yenilenebilir enerji kaynaklarından enerji üretmeye yöneltmektedir. Yenilenebilir enerji kaynakları, yenilenebilir yapıda olmaları ve çevreye zarar vermeme özellikleri ile ön plana çıkmaktadır [1]. Dünya üzerinde fosil yakıtların payının azalması, toplam kurulu güç içerisindeki yenilenebilir enerji ve alternatif enerji kaynaklarının payının düşük olması, ülkelerin enerji kaynaklarını daha verimli kullanmalarına yönelten bir unsur olmuştur.…”
Section: Gi̇ri̇ş (Introducti̇on)unclassified
“…Only national income per capita is used as output variable, while input variables are the percentage of renewable energy sources in electricity generation, energy consumption, CO2 emission, employment rate, and capital. Kupeli and Alp [4] demonstrated the renewable energy performance of G20 countries by data envelopment analysis (DEA) and balanced performance weights method. They concluded that the results of the analysis with the balanced weights model gave more distinctive results than the classical model.…”
Section: Introductionmentioning
confidence: 99%